Optimasi Penjadwalan Mesin Bor Manual pada Produksi Side Chair Menggunakan Metode Shortest Processing Time (SPT) - Indah Rizqiana; Muhammad Choiru Zulfa (Pusat Riset dan Inovasi Nasional, 2024)
CV Mandiri Abadi is a manufacturing industry that operates on a make-to-order system, specifically for side chair products, necessitating a carefully considered scheduling system. Issues with the use of manual drilling machines causing delays in component deliveries to the warehouse prompted an evaluation of optimal production scheduling using the shortest processing time (SPT) method. This study includes detailed calculations to determine average completion time, utilization, average job time, and average job delay. Analysis results show that using manual drilling machines achieved an average completion time of 854.28 minutes, a proposed utilization improvement of 28%, an average job time of 3.46 minutes, and an average delay of 614.14 minutes. This approach is more effective in optimizing processing time and reducing delivery delays. Therefore, the use of the shortest processing time (SPT) method is recommended to improve production performance within the company.